(untitled) (Tanzania Medical Journal, 2017)
Background HIV/AIDS is an ongoing health problem causing still high morbidity and mortality. ART have provided significant clinical benefits leading into reduced mortality and morbidity which requires tolerable, affordable and virologically potent regimens for its durability. Frequent need for change of ART regimes is a challenging problem especially in resource limited settings including Tanzania where there are few options to switch into. This study was designed to determine the frequency, reasons and predictors of ART change in rural Tanzania. Materials and MethodsA cross sectional study was done involving adult HIV positive patients who were initiated on ART between 2005 and 2014. The patients were enrolled serially through routine HIV care and treatment services in eastern rural part of Lake Zone. Information of research interest including demographic data, on diagnosis WHO clinical stage, baseline CD4 counts, year and criterion of ART initiation, initial ART regimen, ART change status, reason for ART regimen change, time on initial ART and enrollment CD4 counts were collected and analyzed using stata version 12. Results A total of 670 patients were enrolled in this study where 220(32.94%) were found to have changed their ART regimen with a first line regimen of 27.5 [IQR=14-38] months. ART toxicity was the most common reason of ART change which 106 (48.18 %) and the odds of having ART change were strongly predicted by age>40, being divorced(OR=2.4 ,p=0.0012), baseline CD4 counts <200 cells/µl (OR=3.9, p<0.001), being initiated on ART due to low CD4<200 cells/µl(OR=2.0, p<0.001) or being initiated on ART with CD4< 350 cells/µl and WHO clinical stage 3(OR=2.2, p<0.001) and d4T based regimen (OR=138, p<0.001)ConclusionsART change is a very frequent problem in rural Tanzania, which is strongly predicted by diagnosis of HIV in older patients, Advanced HIV parameters and d4T based regimens. Universal screening programs to diagnose HIV in earlier ages and in less advanced HIV parameters and subsequent early initiation of less toxic ART regimens could significantly contribute to the reduction of this problem in our setting where we have limited potent options to go for.